Influences of market orientation on sustainability of Islamic microfinance institutions in Malaysia / Soheil Kazemian - Kazemian, Soheil (Institute of Graduate Studies, UiTM, 2015)
For the past century, the human has been suffered by “Poverty”. Several attempts have been made to fight this particular moral challenge. Since last four decades providing small loans for the vulnerable entrepreneurs, which is called as “Microfinance”, has been known as one of the most efficient tools for poverty alleviation. But conventional microfinance or “Microcredit Program” that is based on pre-determined interest may cause more issues for the borrowers, in terms of repaying back the loans. In addition, all contracts based on predetermined interest is strongly prohibited in Islamic rules, which is called “Shariah”. Therefore, for meeting Muslim clients of microfinance products who were not interested in using microcredit, based on avoiding getting predetermined interest, “Islamic Microfinance” was born in South East Asia. But, after three decades and despite of having great market, Islamic microfinance institutions (Islamic MFIs) still face un-sustainability (unsustainable performance) which can result in high poverty rate in this region. The main purpose of this study is to determine influences of three dimensions of market orientation, namely customer orientation, competitor orientation and inter-function coordination on two aspects of sustainability of Islamic microfinance institutions (management sustainability and financial sustainability), in Malaysia that is considered as one of the pioneers in Islamic microfinance business…